PEMBERIAN BEBERAPA KONSENTRASI EKSTRAK BROTOWALI (TinospoacrispaL.) UNTUK MENGENDALIKAN KEONG MAS (PomaceaSP.) PADA TANAMAN PADI (OryzasativaL.) - Devi Kurniawati; Rusli Rustam; J. Hennie Laoh (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2015)
Rice is an important crop in Indonesia, because it contains carbohydrates, protein, fat, fiber, vitamins, and trace elements. Pomacea sp. is a major pest of rice crops in Indonesia. Use of plant molluscicides like Tinospora crispa L. is an alternative to reduce the use of synthetic chemical pesticides. This study aimed to obtain the concentration of Tinospora crispa L. capable of controlling the Pomacea sp. in riceplant. This research was conducted at  plant pest laboratory, Faculty of Agriculture, University of Riau and in the experiments farm of the  Faculty of Agriculture University of Riau.This research using a completely randomized design (CRD), which consist of 5 treatments and 4 replications. There are  extracts Tinospora crispa L.  0 g/l of water, 25 g/l of water, 50 g/l of  water, 75 g/l of water, 95 g/l of water. Concentration of Tinospora crispa L. 75 g/l of  water is able to control Pomacea sp. The result indicated that concentration of 75 g/l of water can cause initial time of death is 12 hours after application,   LT50reach  in  28.25 hours and total mortality 86,99%.   Keyword: Oryza sativa L., Pomacea L., Tinospora crispa L.